Teacher student-specific self-efficacy and its impact on students' academic self-concept, emotional well-being and social inclusion - Eren, Erkan; Yada, Akie; Schwab, Susanne; Savolainen, Hannu (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This study investigates the impact of teachers' student-specific self-efficacy (S-S TSE) on students' perceptions of inclusion, specifically emotional well-being, social inclusion, and academic self-concept, over time. Participants were 42 teachers and 576 students in Austrian inclusive classrooms. Teachers rated S-S TSE using a short form of the Teacher Sense of Efficacy Scale for each student. Students completed the Perceptions of Inclusion Questionnaire (PIQ). Confirmatory factor analyses supported scale validity. All three student outcomes correlated positively with higher S-S TSE. Special educational needs (SEN) status moderated the relationship between S-S TSE and emotional well-being, but not between S-S TSE and social inclusion or academic self-concept.